2017
DOI: 10.1017/s0950268817001625
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing environmental risk factors for West Nile virus in Quebec, Canada, using clinical data in humans and serology in pet dogs

Abstract: The identification of specific environments sustaining emerging arbovirus amplification and transmission to humans is a key component of public health intervention planning. This study aimed at identifying environmental factors associated with West Nile virus (WNV) infections in southern Quebec, Canada, by modelling and jointly interpreting aggregated clinical data in humans and serological data in pet dogs. Environmental risk factors were estimated in humans by negative binomial regression based on a dataset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
(54 reference statements)
3
10
0
Order By: Relevance
“…and agricultural lands, and Cx. pipiens, which is abundant in agricultural, urban and suburban areas), seems consistent with the areas of lower risk identified in the current study [34,35]. Grimstad et al previously reported a correlation between white-tailed deer densities and seroprevalence for JCV in humans [36].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…and agricultural lands, and Cx. pipiens, which is abundant in agricultural, urban and suburban areas), seems consistent with the areas of lower risk identified in the current study [34,35]. Grimstad et al previously reported a correlation between white-tailed deer densities and seroprevalence for JCV in humans [36].…”
Section: Discussionsupporting
confidence: 91%
“…vexans , which is found in abundance in alluvial plains and agricultural lands, and Cx. pipiens , which is abundant in agricultural, urban and suburban areas), seems consistent with the areas of lower risk identified in the current study [34, 35].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, other domestic animals that are housed in close proximity to humans should be investigated as a suitable sentinel. Previous studies showed that dogs could be good sentinels for West Nile virus [ 33 , 34 ], Lyme disease [ 35 ] and other arthropod-borne diseases [ 36 ]. In addition, exposure of dogs to JEV has already been observed in Singapore and Japan [ 8 , 24 ].…”
Section: Discussionmentioning
confidence: 99%